Bonbonnieres in the gallery: (re)presenting sugar in a family gallery space. (8th December 2020) - Boycott‐Garnett, Ruthie; MacRae, Christina; Hackett, Abigail; Otito Tamsho‐Thomas, Tina; Holmes, Rachel
Abstract: This paper charts an on‐going process emerging from a collaborative project between Manchester Art Gallery, and early childhood researchers and practitioners, who are currently working together to develop a new learning space for families. It revolves around the potential of exhibiting a collection of bonbonnieres in this space. These little 18th Century pots, originally filled with sweets or breath mints, are colourful and depict fanciful animals that have an almost cartoon like quality that may resonate with younger children. Yet the contents that once lay inside would have been cut from plantations by the hands of enslaved people. Sugar, in all its sweetness, is intrinsically linked to Britain's colonial history. Sections of a poem by Tina Otito Tamsho‐Thomas (http://revealinghistories.org.uk/smoking‐drinking‐and‐the‐british‐sweet‐tooth/objects/bonbonniere.html ) are emplaced throughout to unambiguously contextualise the bonbonniere as a symbol of enslavement legacy, sugar trade history and British colonialism. Today, excess sugar consumption sits at the heart of the healthy eating agenda, a key priority area for local early years providers. In this paper, textual 'fragments' act as provocations in a series of interdisciplinary conversations that were initiated as a strategy to unsettle the positions of the institution and its curators, educators and practitioners, opening up discursive thinking about the potential of this particular object‐space ensemble. By considering these bonbonnieres as 'vibrant matter' (Bennett, 2010) that can affect and be affected within the gallery space (Tolia‐Kelly, 2016) we ask questions about how these objects might sit alongside the daily interactions that occur in the space in a way that opens up 'discomfort zones'.